IMPLEMENTATION OF LAW NUMBER 35 OF 2014 CONCERNING CHILD PROTECTION AGAINST CHILD VIOLENCE IN THE SCHOOL ENVIRONMENT - Selviana; Dinar Sugiana Fitrayadi; Qotrun Nida (Institut Pendidikan Indonesia, 2022)
Acts of violence occur not only in the community, but also in the school environment. Perpetrators of violence against children usually come from members of the nuclear family, community, government, even friends in the school environment and also teachers. The aim of this research is to determine the implementation of law number 35 of 2014 concerning the protection of children against child violence in the school environment. The research was conducted using qualitative methods. Data collection by conducting interviews, observation and documentation. From the results of this research, it was found that the implementation of Law Number 35 of 2014 concerning child protection has been implemented well, this is proven by the implementation of various components in the policy implementation process such as routine socialization activities, the formation of special teams and assistance to students. The inhibiting factors in implementing prevention and protection policies are the public who still tend to be indifferent and the absence of activities carried out by the relevant agencies. The solution to these inhibiting factors is to continue to coordinate with fellow teaching staff, always provide understanding to students, collaborate with the local police and coordinate with the community.